Phenome-Wide Association Study With Focus on Oral Health Disparities and Individuals Who Did Not Have Cancer - Bezamat, Mariana; Modesto, Adriana; Vieira, Alexandre R. (Frontiers in Dental Medicine, 2021)
The goal of this study was to test if oral health outcomes are associated with the same genetic markers in Blacks and Whites. From a total of 6,100 subjects from the Dental Registry and DNA Repository project, 1,042 individuals who self-identified as White and 266 as Black without a history of cancer were included in this analysis. Genotyping data from IRE1 – rs196929, RHEB – rs2374261 and rs1109089, AXIN2 – rs2240308 and rs11867417, and RPTOR – rs4396582, present in cell regulatory pathways, were analyzed. We ran separate analyses in self-reported Black and White groups to reduce possible confounding effects of population stratification. Internal diagnostic codes from our dental registry were converted into Phecodes in order to run the analysis using the PheWAS package, installed in R Studio software. Periodontitis was associated with RHEB in both Black and White patients, with the minor allele increasing the likelihood of developing periodontitis in the Whites and yielding a protective effect in the Black individuals. The presence of ulcers and gingivitis were associated with RPTOR and AXIN2, respectively, in the Whites, but an association was not detected for the Blacks. On the other hand, phenotypes such as dental fracture, diseases of the tongue, attrition, erosion, abrasion, fordyce granules, and torus and exostosis were uniquely associated with the Blacks. Periodontitis associated with RHEB in both Blacks and Whites, and associations found in Black individuals may be the result of social disparities that lead to higher levels of stress, and these observed differences require further study.